The Impact of Teachers' Oral Corrective Feedback (OCF) to Students' Anxiety in Speaking Class - Riki Ruswandi; Revita Fitrianti Sukma; Nafisa Fadhilah Rahim (JEELS (Journal of English Education and Linguistics Studies), 2025)
Teachers usually provide Oral Corrective Feedback (OCF) to students during classroom learning, especially when learning English, which has language skills such as reading, writing, listening, and speaking. It causes anxiety in students, which leads to fear, low self-esteem, lack of confidence, and even unmotivated. The study aims to determine the impact of the application of OCF on students' anxiety when speaking English in class. This research approach used a quantitative approach. This study used a pre-experimental with one group before- and-after design. The data were collected from 34 students of class X in the second semester at SMA 1 Ciparay. The data were collected by conducting observations, tests (pretest and posttest, and questionnaires. The data were analyzed using a paired sample test technique to determine students' speaking ability differences before and after treatment. The findings of the paired sample test indicated a substantial change in the anxiety levels of the students before and after OCF was given. Based on the hypothesis test results, the significance is (t = <.001, p < 0.05). It suggests a significant improvement in students' speaking ability compared to before and after receiving OCF. The results of this study also indicated that the use of OCF was able to reduce students' anxiety, especially when they had to speak in front of the class.